Propping up Europe? - Jean Pisani-Ferry; Guntram B. Wolff (Bruegel, 2012)
The Bank of England, the Federal Reserve (Fed) and the European Central Bank (ECB) have responded to the crisis with exceptional initiatives resulting in a major increase in their balance sheets. After the ECB's end-2011 launch of three-year bank refinancing (LTRO), there has been speculation that all three have de facto embarked on 'quantitative easing'. However, major differences remain: the Bank of England and Fed have mostly relied on large-scale purchases of government bonds, while the ECB has relied on lending to financial institutions with repurchase agreements of collateral (repos). The LTRO has successfully mitigated funding needs and reduced interbank stress, and has had a significant impact on sovereign bond yields in southern euro-area countries, and increased southern banks' government debt holdings, while northern banks have reduced sovereign exposure. The LTRO has had only weak effects on funding for households and non-financial corporations; credit dynamics remain weak particularly in the southern euro area. Underlying structural problems relating to banks, the macroeconomic adjustment and the euro area's governance need to be addressed before financial stability and economic growth can return. Monetary policy cannot fundamentally address these problems and is made less effective by economic/institutional heterogeneity.
Keywords: 330; Geldmarkt; Öffentliche Anleihe; Geldpolitik; Zentralbank; Eurozone; EU-Staaten; Großbritannien; USA